ORMULASI TABLET KUNYAH DARI EKSTRAK ETANOL CABAI RAWIT (Capsicum frutescens L.) DENGAN VARIASI PENGISI MANITOL – DEKSTROSA MENGGUNAKAN METODE GRANULASI BASAH - ., Kukuh Permadi (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2014)
Cabai rawit (Capsicum frutescens L.) is a plant that contain flavonoid and had anantioxidant activity. Cabai rawit extracts were made as a chewable tablet with purpose toincrease the acceptablet of herb medicine in the society. This research was done to learn theeffect of variation of filler combination mannitol-dextrose. The chewable tablets were made intothree formulas, FI with combination of mannitol-dextrose (80:20%); FII (50:50%); and FIII(20:80%). The chewable tablet then got physical evaluation such as physical appearance, sizeuniformity, weight uniformity, hardness, friability, disintegration time and taste response test.The results of the evaluation was the variation of filler combination affect the hardness of tablet,friability, desintegration and the taste of tablet. The best result of physical evaluation ofchewable was FII with combination of mannitol-dextrose (50:50%). Keywords : Cabai rawit, mannitol, dextrose, chewable tablet, wet granulation